Application of color-coded digital subtraction angiography in treatment of indirect carotid-cavernous fistulas: Initial experience - Lin, Chung-Jung; Luo, Chao-Bao; Hung, Sheng-Che; Guo, Wan-Yuo; Chang, Feng-Chi; Beilner, Janina; Kowarschik, Markus; Chu, Wei-Fa; Chang, Cheng-Yen (Journal of the Chinese Medical Association, 2013)
Parametric-colored digital subtraction angiography using Tmax is almost a routine angiographic imaging procedure, currently. The current feasibility study is aimed to using the imaging to monitor treatment effects while embolizing indirect carotid-cavernous fistulas (CCF). Ten patients with CCFs receiving embolization and 40 patients with normal circulation time were recruited. Their color-coded DSAs were used to define the Tmax of selected intravascular ROIs. A total of 19 ROIs in the internal carotid artery (ICA) (cervical segment of ICA in AP view (I0), cavernous segment of ICA in AP view (I1), supraclinoid segment of ICA in AP view (I2) and cervical segment of ICA in lateral view (I0′), cavernous portion of ICA in lateral view (IA), supraclinoid portion of ICA in lateral view (IB)), ACA (first segment of anterior cerebral artery, second segment of anterior cerebral artery (A1, A2)), middle cerebral vein (MCA) first segment of MCA ((M1), second segment of MCA (M2)), frontal vein (FV), parietal vein (PV), superior sagittal sinus (SSS), sigmoid sinus (SS), internal jugular vein (JV), fistula, superior ophthalmic vein (SOV), inferior petrosal vein (IPS), and MCV were selected. Relative Tmax was defined as the Tmax at selected ROIs minus Tmax at I0 or I0′. An intergroup comparison between the normal and treatment groups and pre- and post-treatment comparison of the peri-therapeutic rTmax for the treatment group were performed. rTmax's for the normal group were as follows: Anterior-posterior view: I1: 0.16, I2: 0.32, A1: 0.31, M1: 0.35, SSS: 6.16, SS: 6.56, and MCV: 3.86 seconds. Lateral view: IA: 0.05, IB: 0.20, A2: 0.53, M2: 0.95, FV: 4.84, PV: 5.12, IPS: 4.62, JV: 6.81, and MCV: 3.86 seconds. Before embolization, rTmax of the IPS, SS, and JV for the treatment group were shortened (p < 0.05). No rTmaxs for any arterial ROIs in the fistula group were significantly different. After embolization, the rTmaxs for all venous ROIs returned to normal except for two which were partially obliterated. This postprocessing method does not require extra radiation exposure and contrast media. It facilitates real-time hemodyamic monitoring and may help determining the endpoint of embolization, which increases patient safety.